DESIGN AND IMPLEMENTATION OF A MOBILE ROBOT PLATFORM FOR IDENTIFICATION OF LAND MINES IN VARIOUS FIELDS OF COLOMBIA - Sanabria Bustos, J. R (2015)
In the present time the mine clearance by the security forces is considered a job with a high mortality rate. The purpose of this article was to develop and implement a robotic platform remote control for identification of antipersonnel landmines in various fields; starting from an obstacle avoidance system, for this propose we using the algorithm VFH (Vector Field Histogram) through the LabVIEW Robotics software. The results have showed that the caterpillar type traction system allows better movement, more grip in all fields compared to the type wheel drive system, plus 87.5% accuracy in identifying mines was obtained from a set of 8 different materials, compared with the currently used system MICRONTA 4003. The implemented system contributes to the detection of dangerous objects on different grounds, becoming an alternative to reduce mortality rates in demining.